PENINGKATAN PENDIDIKAN KARAKTER DALAM UPAYA MEMBANGUN BUDAYA HUKUM YANG HUMANIS DAN RELIGIUS DI KALANGAN REMAJA - Ahmad Munawaru Zaman; Dhony Setiawan; Mukhamad Khotib Arifai; Abdul Hadi; Dadan Herdiana (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Character education is a system of inculcating character values to school members which includes components of knowledge, awareness or willingness, and actions to implement these values, both towards God Almighty (YME), oneself, others, the environment, and nationality. so that we become human beings. Character education aims to form individuals who are moral, have good personalities, have character and are dignified through the education system.This Community Service is held at Mathlaul Anwar Vocational School which is located on Jl. Raya Mauk Km.16, Buaran Jati, Kec. Sukadiri, Tangerang Regency, Banten. This community service is carried out in order to fulfill the obligations of the Tri Dharma of Higher Education. This community service is carried out by lecturers and students of the Infirmatics Engineering Study Program, Faculty of Engineering, University of Pamulang. Lecturers and students have been given assignments according to their respective roles.Currently, it is undeniable that the number of juvenile delinquency is increasing, such as drug abuse among teenagers, brawls, promiscuity, and others. Therefore, this Community Service aims to provide an understanding of Mathlaul Anwar Vocational School students about character education so that students can become graduates who have high intellectuality and also have strong characters so that they can implement these characters in everyday life in order to support the creation of culture. humanist and religious law of society.Community service is carried out by the extension method, where the theme of the counseling taken in this PKM activity is about improving character education in an effort to build a humanist and religious legal culture among teenagers. Technical counseling is divided into two parts, namely through material presentation and question and answer/discussion.After this Community Service activity, it is hoped that Mathlaul Anwar Vocational School students can understand more about the importance of character in real life so that they will later become law-abiding individuals and have a humanist and religious spirit. The results of this Community Service activity will be published in the KOMMAS Journal and will be published on online media. Keywords: Community Service, Character Education, Pamulang University